FTIR study of ageing of γ-irradiated biopharmaceutical EVA based film. (July 2016) - Gaston, Fanny; Dupuy, Nathalie; Marque, Sylvain R.A.; Barbaroux, Magali; Dorey, Samuel
Abstract: In the biopharmaceutical and biotechnological industries, disposable plastic bags are used to replace stainless steel vessels. A single-use bag is made up of a film, very often a multilayer structure, which provides good sealability of the contact layer, robustness and barrier to gas. Ethylene vinyl acetate (EVA) is one of the materials constitutive of this multilayer structure. Because these single-use plastic bags have to be sterile upon delivery, they are irradiated at doses between 25 and 45 kGy. The present work aims to investigate the effects of γ-irradiation on the surface of the multilayer film by Fourier Transform Infrared (FTIR) spectroscopy. Optical spectroscopy techniques are of great interest for chemical analysis and are used to obtain information on the composition of materials, in our present case polymers. The chemical changes are monitored over time (up to 12 months) after γ-irradiation (up to 270 kGy) using FTIR to study the composition and stability of the film. The chemometric method called Principal Component Analysis (PCA) is used to highlight the changes in shift or intensity in the oxidation zone and in the unsaturated group zone. Graphical abstract: Highlights: γ-ray sterilization of single-use plastic bags for biotechnological and biopharmaceutical applications. Use of ATR-FTIR spectroscopy to monitor the modifications of γ-irradiated polymers over time. Chemometric methods make it possible to highlight slight spectral variations after multiple irradiation with γ-doses.